Implementing Total Quality Management through the Plan-Do-Check-Act Cycle to Enhance Educational Quality - Agus Salim Dasuki; Desi Puspitosari; Mutiara Rizka Ahmad (International Journal of Management, Innovation, and Education, 2024)
Improving the quality of higher education requires a systematic and integrated management approach. This study explores the implementation of Total Quality Management (TQM) through the Plan-Do-Check-Act (PDCA) cycle as a continuous improvement strategy at Universitas Darma Persada (UNSADA), Jakarta. The research emphasizes how PDCA serves as an effective operational framework for realizing the principles of TQM within an educational context, focusing on planning, implementation, evaluation, and corrective actions. The integration of the PDCA method enables the university to strengthen quality assurance mechanisms, promote organizational restructuring, and foster a culture of excellence aligned with Japanese management philosophy. Using a descriptive qualitative approach, the study examines data collected from institutional reports, policy documents, and interviews with quality assurance units and academic leaders. The findings indicate that consistent PDCA implementation enhances administrative efficiency, teaching effectiveness, and stakeholder engagement. Continuous improvement initiatives and quality standardization have also contributed to better accreditation outcomes and stronger institutional collaboration with industrial partners such as Toyota. The study concludes that embedding PDCA-driven TQM practices fosters sustainable quality development, institutional agility, and accountability in higher education management.